A Mini Review on The Biomass Energy Implementation from Economic Perspective in Indonesia - Zin Min Tun; Marcelinus Christwardana; Rocky Adiguna; H. Hadiyanto; Jaka Windarta (Journal of Bioresources and Environmental Sciences, 2023)
The economically feasible study has become an important factor in today's societies due to achieve the well-being of people. The study analyzed the economic perspective of biomass energy from several secondary data locally and globally. The main target of this study aims to explore the economic perspective of biomass energy in Indonesia. The purpose of this study evaluates from many several economic advantages of the utilization of biomass energy such as economic sustainability, and job creation, and the last one is achieving sustainable development goals. Intensive exposure to several analysis factors of the advantages of modern biomass energy that is leading to economically feasible sustainability for the environment and local people in Indonesia. Moreover, it was found that the relationship between biomass energy and sustainable development significantly related to and supported the achievement of United Nation – Sustainable Development Goals (UN SDGs). Based on analyzing the biomass energy and economic strong effect on social development. After this, found significant benefits of biomass energy by creating local income, health care, school, and transportation as well as agriculture. These conclusions are discussed from many literature predictions about the future perspective of the relationship between biomass energy and economics. Recommendations encourage to government, investors, and stakeholders to involve biomass energy which is aim to achieve renewable energy targets. This research will provide more understanding of the several benefits of biomass energy and also to policymakers and investors to the intention of economic growth of biomass energy.